Bhabinkamtibmas Efforts Through the Sambang Door to Door System in Preventing Theoring in the Jurisdiction of the Klaten - Yosep Jadi Parlindungan Pasaribu (Advances in Police Science Research Journal, 2022)
The focus of the research in this final project is the efforts of Bhabinkamtibmas through a door to door system to prevent theft in the Klaten Police Legal Area. The focus of this research is considered important because the number of theft incidents in the Klaten Police District is still high. Therefore, the Bhabinkamtibmas in the Legal Territory of the Klaten Police is trying to go through a door-to-door system with reference to Perkap No. 7 of 2021 concerning Bhabinkamtibmas. This study aims to: (1) describe how the efforts of Bhabinkamtibmas through the door-to-door system to prevent cases of theft, (2) describe how to increase the efforts of Bhabinkamtibmas through the door-to-door system to prevent theft in the Klaten Police Legal Area. In the conceptual literature to analyze the problems above, several theories are used in this study, namely; Management theory (POAC and 5M) and communication theory. While the concepts used are; the Bhabinkamtibmas concept and the door to door system. In this study, qualitative methods with descriptive analysis were used to process data and field research to obtain data by observing participant as observer. Primary and secondary data sources use data triangulation to obtain data validity. The findings of this study are; (1) the implementation of the door to door system by Bhabinkamtibmas in accordance with Perkap No. 7 of 2021 concerning Bhabinkamtibmas. Lack of supervision carried out, Bhabinkamtibmas lacked discipline in following APP, and Bhabinkamtibmas did not reach the number of implementation targets, (2) Bhabinkamtibmas efforts in implementing the door to door system hampered due to the number of personnel, alsus, educational background of Bhabinkamtibmas, and budget. The conclusions in this final project, (1) The door to door system visit is still not effective and efficient based on Perkap No. 7 of 2021 (2) efforts to optimize the door to door system visit are still hampered due to lack of coordination between the Bhabinkamtibmas Kanit and the Head of other functions.